1981
DOI: 10.1136/bmj.283.6287.343
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of breathlessness: contrasting effects of diazepam and promethazine in pink puffers.

Abstract: Fifteen out of 18 "pink and puffing" patients completed a double-blind, placebo-controlled cross-over trial of diazepam and promethazine for breathlessness and reduced exercise tolerance. Dosages were 25 mg and 125 mg daily, respectively, and each course lasted two weeks. Patients with psychiatric or other major medical histories were excluded.Of the three patients who did not complete the trial, one died during an exacerbation of breathlessness while taking diazepam, one was withdrawn because of mild hypercap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 13 publications
0
62
0
4
Order By: Relevance
“…Enthusiasm for the therapeutic use of diazepam was engendered by the initial report of MITCHELL-HEGGS et al [61], who reported a "striking" reduction in breathlessness (subjectively assessed) in four male patients with the "pink puffer syndrome" when treated with this drug. This finding has not been sustained in other studies [62,63]. This syndrome (severe airflow obstruction, relatively preserved gas exchange and severe breathlessness) probably merges with those subjects considered to have disproportionate breathlessness by BURNS and HOWELL [60].…”
Section: The Use Of Drugs To Alter the Perception Of Breathlessnessmentioning
confidence: 66%
See 1 more Smart Citation
“…Enthusiasm for the therapeutic use of diazepam was engendered by the initial report of MITCHELL-HEGGS et al [61], who reported a "striking" reduction in breathlessness (subjectively assessed) in four male patients with the "pink puffer syndrome" when treated with this drug. This finding has not been sustained in other studies [62,63]. This syndrome (severe airflow obstruction, relatively preserved gas exchange and severe breathlessness) probably merges with those subjects considered to have disproportionate breathlessness by BURNS and HOWELL [60].…”
Section: The Use Of Drugs To Alter the Perception Of Breathlessnessmentioning
confidence: 66%
“…Treatment of breathlessness is most effective when the primary cause can be identified and modified, but in those conditions in which treatment currently has little to offer, it is logical to explore the feasibility of modifying the perception of breathlessness in order to relieve distress. Many drugs, such as hydrocodeine [52][53][54][55], morphine [56][57][58][59], diazepam [60][61][62][63] and promethazine [62,63], have been tested for their ability to relieve intractable breathlessness, with inconclusive results. Relief when obtained can, in most cases, be adequately explained by a reduction in respiratory work without the need to postulate any alteration in the perceptive mechanism or ability.…”
Section: The Use Of Drugs To Alter the Perception Of Breathlessnessmentioning
confidence: 99%
“…A number of other pharmacologic agents, including anxiolytics (251)(252)(253), antidepressants (254), phenothiazines (237,255), indomethacin (256,257), inhaled topical anesthetics (258,259), nitrous oxide (260), and sodium bicarbonate (261), have been found to be ineffective or lack sufficient data to recommend their use (247).…”
Section: Treatmentmentioning
confidence: 99%
“…Opioids have been the most widely studied agent in the treatment of dyspnea (204,230,235). Short-term administration reduces breathlessness in patients with a variety of conditions, including advanced COPD (236,237), interstitial lung disease (238), cancer (239), and chronic heart failure (240). However, evidence of long-term efficacy is limited and conflicting (241,242).…”
Section: Treatmentmentioning
confidence: 99%
“…In the earlier study on patients (Woodcock et al, 1981) promethazine was given chronically at a daily dose of 125 mg and several of the patients ex- (Bradley et al, 1966), Laros & Bergstein (1982) have suggested that chlorpromazine might specifically reduce breathlessness by lowering the sensory input to the mesencephalon. Killam & Killam (1958) argued that chlorpromazine increased the selective inhibition by the reticular formation of the afferent sensory information.…”
Section: Discussionmentioning
confidence: 99%